Memoirs of a revolutionist. [With introd. by G. Brandes]. With a new introd. and notes by N. Walter (Dover Publications, 1971)
With index and prt. An unabridged and unaltered republication of the ed. publ. in 1899, by Houghton, Miffin, Boston etc.